Desenvolvimento de esponjas de quitosana/policaprolactona para uso em odontologia - Muniz, Isis de Araújo Ferreira (2018)
Introduction: Tissue engineering allows combining biomaterials, cells, growth factors, and differentiation with the goal of improving or even restoring tissue or organ functions. Among these biomaterials, chitosan is a possible candidate for application in the treatment of infectious-inflammatory oral diseases, because of its biocompatibility, anti-inflammatory and antimicrobial properties. Objective: To characterize and evaluate the antimicrobial activity of sponges based on chitosan and polycaprolactone (PCL). Method: The sponges were previously prepared in the following proportions (v / v): 100% chitosan (pure Q); 75% chitosan and 25% PCL (75/25); 50% chitosan and 50% PCL (50/50), 25% chitosan and 75% PCL (25/75) and subsequent lyophilization. The samples were characterized by scanning electron microscopy (SEM), perfilometry, contact angle, degradation in PBS and UV-VIS spectroscopy. Evaluation of antimicrobial effect was performed using halo inhibition or macrodilution test for S. mutans (ATCCUA159) and S. sanguinis (ATCCBAA1455). Results: SEM analysis showed the interconnectivity of the pores, as well as the degree of porosity, which increased the higher the proportion of PCL in the sponges. In the perfilometry, through the Ra parameter, a significant difference of all groups was observed in relation to 25/75 (p <0.05), which presented the greatest roughness. The samples presented a highly hydrophilic character, so the contact angle was not measured. The sponges presented degradation after 28 days of immersion in PBS, and the UV-VIS detected the chitosan spectrum proving its release. In the macrodilution analysis, a reduction in the counts of CFUs was observed for S. mutans in the proportions of 75/25 and 50/50, and for S. sanguinis for all proportions in relation to the control. Conclusion: The characterization of PCL and chitosan sponges showed porosity, roughness and hydrophilicity, especially the proportion (50/50), with antimicrobial action. New studies for the incorporation of bioactive substances or antimicrobial and/or anti-inflammatory potential should be performed for the development of these scaffolds and future application in oral infections